Methylation of the N‐terminal histidine protects a lytic polysaccharide monooxygenase from auto‐oxidative inactivation. (18th October 2018) - Petrović, Dejan M.; Bissaro, Bastien; Chylenski, Piotr; Skaugen, Morten; Sørlie, Morten; Jensen, Marianne S.; Aachmann, Finn L.; Courtade, Gaston; Várnai, Anikó; Eijsink, Vincent G.H.
Abstract: The catalytically crucial N‐terminal histidine (His1) of fungal lytic polysaccharide monooxygenases (LPMOs) is post‐translationally modified to carry a methylation. The functional role of this methylation remains unknown. We have carried out an in‐depth functional comparison of two variants of a family AA9 LPMO from Thermoascus aurantiacus ( Ta LPMO9A), one with, and one without the methylation on His1. Various activity assays showed that the two enzyme variants are identical in terms of substrate preferences, cleavage specificities and the ability to activate molecular oxygen. During the course of this work, new functional features of Ta LPMO9A were discovered, in particular the ability to cleave xyloglucan, and these features were identical for both variants. Using a variety of techniques, we further found that methylation has minimal effects on the p K a of His1, the affinity for copper and the redox potential of bound copper. The two LPMOs did, however, show clear differences in their resistance against oxidative damage. Studies with added hydrogen peroxide confirmed recent claims that low concentrations of H2 O2 boost LPMO activity, whereas excess H2 O2 leads to LPMO inactivation. The methylated variant of Ta LPMO9A, produced in Aspergillus oryzae, was more resistant to excess H2 O2 and showed better process performance when using conditions that promote generation of reactive‐oxygen species. LPMOs need to protect themselves from reactive oxygen species generated in their active sites and this study shows that methylation of the fully conserved N‐terminal histidine provides such protection.